2020
DOI: 10.1590/0103-8478cr20190260
|View full text |Cite
|
Sign up to set email alerts
|

Rice farmer’s poverty and its determinants: evidence from Dogofiri village of Office du Niger zone in Mali

Abstract: The aim of this research was to contribute to a better understanding of rice farmer’s poverty of Office du Niger (ON) in Mali at village-level. Data were collected through survey with 110 head family farms in the village of Dogofiri. Quantitative data were analyzed using descriptive statistics. Multiple linear regression models were used to analyze the main determinants of poverty. Results indicated that the factors of physical capital and human capital as well as government policy have a significant influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This finding is in agreement with Akintayo et al (2010) that reported rice farmers in Niger state employed sub-optimal recommended management practices; seed rate, fertilizers and agrochemicals for weed control. This could be responsible for the low yields obtained by rice farmers in the zone as also agreed by Coulibaly et al (2020).…”
Section: Management Practices Adopted By Rice Farmersmentioning
confidence: 68%
“…This finding is in agreement with Akintayo et al (2010) that reported rice farmers in Niger state employed sub-optimal recommended management practices; seed rate, fertilizers and agrochemicals for weed control. This could be responsible for the low yields obtained by rice farmers in the zone as also agreed by Coulibaly et al (2020).…”
Section: Management Practices Adopted By Rice Farmersmentioning
confidence: 68%